Coastal rehabilitation through the implementation of government policy: Case study in Karawang Regency, West Java, Indonesia - Medi Nopiana; Fredinan Yulianda; Sulistiono Sulistiono; Achmad Fahrudin (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2020)
Damage on the coastal area of Karawang Regency requires improvement efforts through the implementation of several government policies. However, modification of the policy developed to manage natural resources in the sea was one of the causes of non-optimal role of the government in rehabilitating coastal areas. This study aims to analyze the effectiveness of implemented regency government policies in achieving successful coastal rehabilitation. The data obtained were analyzed using descriptive analysis with a quantitative approach. The results shows the capacity of the Karawang Regency Government was still low in supporting the successful implementation of coastal rehabilitation policies. The Karawang Regency Government needs to collaborate with other stakeholders, redistribute employees, and encourage increase on education and training for staff.